Association between Systolic Blood Pressure after Thrombolysis and Early Neurological Improvement in Ischaemic Stroke Patients. Issue 3 (May 2017) - Seok, J; Lee, JS; Jeong, KY; Lee, CM
Introduction: This study aimed to evaluate the relationship between systolic blood pressures (SBPs) within 12 hours after intravenous recombinant tissue plasminogen activator (rtPA) treatment and early neurological outcomes. Methods: This was a retrospective observational study of acute ischaemic stroke (AIS) patients who received intravenous rtPA administration. SBPs at the time of rtPA bolus and thereafter every hour were collected. The mean, standard deviation, and coefficient of variation values of SBP during the periods of 0-2 h, 2-6 h, and 6-12 h were calculated. The primary outcome was major neurologic improvement (MNI) at 24 hours after thrombolysis. Results: Serial measures of SBPs revealed different 12-hour courses between the patients with and without MNI. The difference of SBP tendency was statistically significant (p=0.013). In univariate analysis, patients with MNI showed lower levels of mean SBPs during the periods of 2-6 h and 6-12 h (p=0.030 and p=0.005, respectively), and higher frequency of very early neurologic improvement (VENI) at the end of rtPA infusion (p<0.001). In logistic regression analysis, VENI at 1 h, mean SBP value during 6-12 h, and atrial fibrillation were independently related to MNI at 24 h. Conclusions: SBP level during the first 12 hours after intravenous rtPA treatment may be an important clinical factor that is associated with early neurological improvement of AIS patients.